Analysis and update of the human aldehyde dehydrogenase (ALDH) gene family - Vasiliou, Vasilis (BioMed Central, 2005)
The aldehyde dehydrogenase (ALDH) gene superfamily encodes enzymes that are critical for certain life processes and detoxification via the NAD(P)(+)-dependent oxidation of numerous endogenous and exogenous aldehyde substrates, including pharmaceuticals and environmental pollutants. Analysis of the ALDH gene superfamily in the latest databases showed that the human genome contains 19 putatively functional genes and three pseudogenes. A number of ALDH genes are upregulated as a part of the oxidative stress response and inexplicably overexpressed in various tumours, leading to problems during cancer chemotherapy. Mutations in ALDH genes cause inborn errors of metabolism -- such as the Sjögren - Larsson syndrome, type II hyperprolinaemia and γ-hydroxybutyric aciduria -- and are likely to contribute to several complex diseases, including cancer and Alzheimer's disease. The ALDH gene products appear to be multifunctional proteins, possessing both catalytic and non-catalytic properties.